Analisis Kemampuan Mahasiswa dalam Penulisan Karya Ilmiah Melalui Perspektif Literasi Data di Perguruan Tinggi - Irma Arifah; Suprapti Suprapti (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Scientific writing serves as a platform for students to convey their knowledge, experiences, and information to readers. Data literacy is a crucial tool that aids students in developing, analyzing, and concluding the data they have gathered into well-constructed scientific writing. This research aims to describe students' ability to write scientific papers with respect to data literacy in higher education institutions. To gather research data, the researchers employed a qualitative descriptive method. The data in this study represent the challenges or difficulties faced by the students. Data collection techniques include careful observation and reading of these papers, and documentation techniques involve marking or noting significant parts of the students' scientific works. Data analysis involved mapping frequent errors and calculating the percentage of these errors based on the characteristics of scientific writing. The results indicated that students' ability to write scientific papers remains low, particularly in the areas of idea development and discussion. The following percentages illustrate the students' writing abilities and data literacy: 14.25% of students can develop ideas, with 19% data literacy at the analysis stage. The ability to write the results and discussion sections of scientific papers is at 13.40%, with 12.40% data literacy at the conclusion-making stage. In the concluding section, 71.20% of students accurately write conclusions, with 67.60% data literacy at the reading stage. This study's findings highlight persistent issues in idea development and the results and discussion sections in scientific writing at higher education institutions. Further research should focus on these sections to address the difficulties identified in this study.